2017
DOI: 10.1007/s00706-017-1958-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of perovskite FAPbBr3−x I x thin films for solar cells

Abstract: FAPbI3, FAPbBr3 and FAPbBr3-xIx perovskite thin films were 9 produced in a single step from a solution containing a mixture of FAI, PbI2, 10FABr, and PbBr2 (FA=Formamidinium). FAPbBr3-xIx perovskite thin films 11were deposited onto ITO-coated glass substrates by spin coating. X-ray 12 diffraction analyses confirmed that these thin film perovskites crystallize in the 13 cubic phase (Pm-3m) for all composition range 0 ≤ x ≤ 3. Mixed lead 14 perovskites showed a high absorbance in the UV-vis range. The optical 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 50 publications
5
28
0
Order By: Relevance
“…This was further supported by the small full width at half maximum of the [110] peak in the X‐ray diffraction spectroscopy (XRD) spectra (Figure 5b; Table S3, Supporting Information). [ 54–56 ] This reveals that the higher J SC of the virus‐added PSCs came mainly from the combined effect of the scattering and the grain size enlargement. In addition, the marginally higher J SC value obtained from the KKK‐type virus‐added PSCs than from the wild‐type virus‐added PSCs is probably resulted from slightly larger and more uniform perovskite grain size, giving rise to a better collection of the dissociated charge.…”
Section: Resultsmentioning
confidence: 98%
“…This was further supported by the small full width at half maximum of the [110] peak in the X‐ray diffraction spectroscopy (XRD) spectra (Figure 5b; Table S3, Supporting Information). [ 54–56 ] This reveals that the higher J SC of the virus‐added PSCs came mainly from the combined effect of the scattering and the grain size enlargement. In addition, the marginally higher J SC value obtained from the KKK‐type virus‐added PSCs than from the wild‐type virus‐added PSCs is probably resulted from slightly larger and more uniform perovskite grain size, giving rise to a better collection of the dissociated charge.…”
Section: Resultsmentioning
confidence: 98%
“…As light blueshift can be observed with the increaseo fcation (MA, Cs, or Rb) contents, which is in good agreementw ith the corresponding PL peaks in Figure 3b.C ompared with MA x -FA, the Cs x -FAa nd Rb x -FAf ilms present ab lueshift in the absorption band edge because of the smalleri onic radius of Cs and Rb. [38,39] The second phase (orange-red phase) displays aX RD diffraction peak at 2q = 12.238 (Figure 2e). [38,39] The second phase (orange-red phase) displays aX RD diffraction peak at 2q = 12.238 (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…The same trend can be found in the normalized PL spectra.I nterestingly,asecond peak can be found in the PL spectra of the FA film (Figure 3b), which is caused by the phase segregation generating Br-rich and Br-free regions. [38,39] The second phase (orange-red phase) displays aX RD diffraction peak at 2q = 12.238 (Figure 2e). This is intrinsic to all ( ChemSusChem 2018ChemSusChem , 11,2436ChemSusChem -2443 www.chemsuschem.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim second PL peak is observed.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Despite showing high efficiency, prototype perovskite materials such as MAPbX 3 and FAPbX 3 (where MA ¼ methylammonium; FA ¼ formamidinium; X ¼ Br, I) suffer from phase instability, poor reproducibility, and thermal instability. [10][11][12] Saidaminov et al 13 found lattice strain in perovskite induces point defects leading to structural degradation and PLQY quenching. Lattice perfection can be improved by the addition of inorganic Cs + that improves phase stability by strain relaxation leading to more reproducible optoelectronic devices with improved thermal stability.…”
Section: Introductionmentioning
confidence: 99%